Pemberdayaan Kelompok Wanita Tani di Desa Sukadadi Melalui Kerjasama dan Manajemen Keuangan - Saleh, Yuliana; Rahmalia, Dian; Rani Mellya Sari, I; Sekartiara Syafani, Tyas (Agriculture Faculty, Universitas Lampung, 2025)
The community service activities carried out by the Agribusiness Department of the Faculty of Agriculture, University of Lampung, in Sukadadi Village, Gedong Tataan District, Pesawaran Regency, aim to strengthen the institutional and managerial capacity of the Women Farmers Group (KWT) through training in cooperation and financial management. This activity was motivated by the weak group dynamics, low leadership skills, minimal member participation in decision-making, and the lack of orderly financial record-keeping systems in most KWTs. The program was implemented over 9 months (January–September 2025) involving three active KWTs, namely KWT Tunas Indah, KWT Tunas Ceria, and KWT Tunas Indah 2. The implementation methods included interactive material delivery, case study simulations, pre-tests and post-tests, as well as follow-up assistance. The evaluation results showed a significant improvement in the participants' understanding and skills. The average pre-test score of 50 increased to 82.30 on the post-test, or an increase of 32.30 (64.60%). The learning method that combines interactive lectures, discussions, simulations, and educational games has proven to be effective for people with non-academic backgrounds. In addition to improving technical skills, these activities also foster social solidarity, self-confidence, and transparency in group financial management. Follow-up assistance shows that all participating women's groups have independently implemented simple cash recording. This program has successfully empowered women farmers through institutional and creative economic initiatives that support sustainable agricultural development at the village level.